EFEKTIFITAS BIOAMELIORAN SEBAGAI PEMBENAH TANAH PADA TANAMAN CABAI KERITING (Capsicum annuum L.) - Mu'minah Mu'minah; Junyah Leli Isnaini; Baso Darwisah; Abdul Mutalib; Andi Besse Poleuleng; Syarif Ismail; Andi Mega Ayu Lestari; Muhammad Nasrul (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2023)
Bioameliorant as a soil enhancer acts as a bioferlizer because it can provide fertility to the soil and improve the physical, chemical and biological properties of the soil. This research aims to see and determine the effect of various concentrations of Bioameliorant (soil enhancer) and organic materials on the growth of curly red chili plants. This study used a Randomized Block Design (RAK) with 4 doses of bioameliorant treatment, namely: control (B0) without bioameliorant, (B1) 10 ml/l water (B2) 15 ml/l water and (B3) 20 ml/l water. Each treatment consisted of 2 units consisting of 3 groups so there were 24 experimental units. The dose of organic material given is 30 tons/ha or the equivalent of 53 grams/polybag. The experimental results showed that giving bioameliorant to curly chili plants with a concentration (B3) of 20 ml/l of water showed the highest growth in plant height (109.66 cm), large number of leaves (31.33), large number of branches (15.33 branches). , the highest number of fruit (22.66 pieces) and the heaviest fruit weight (61.96 grams) and the heaviest root weight (18.02 grams). Based on the experimental results, it can be concluded that the application of bioameliorants (soil amendments) and organic materials gave the best results in treatment with a concentration of 20 ml/liter of water on the growth of curly chili plant